2015
DOI: 10.1155/2015/616109
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran Associated Leukocytoclastic Vasculitis

Abstract: Common side effects of dabigatran are bleeding, bruising, nausea, diarrhea, and abdomen discomfort. Skin reactions were not often noted (<0.1%). We report a case of 70-year-old male who developed dabigatran related skin reaction resistant to usual therapy. Skin biopsy revealed leukocytoclastic vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…Renal and hepatic adverse events are among the emerging DOAC safety issues [ 17 ]. Rare but severe skin adverse events, such as vasculitis, have also been reported in dabigatran-treated patients [ 19 – 21 ]. Furthermore, non-bleeding adverse events, including gastrointestinal symptoms such as dyspepsia, reported in dabigatran-treated patients [ 22 24 ], have been found to be one of the main reasons for permanent DOAC discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…Renal and hepatic adverse events are among the emerging DOAC safety issues [ 17 ]. Rare but severe skin adverse events, such as vasculitis, have also been reported in dabigatran-treated patients [ 19 – 21 ]. Furthermore, non-bleeding adverse events, including gastrointestinal symptoms such as dyspepsia, reported in dabigatran-treated patients [ 22 24 ], have been found to be one of the main reasons for permanent DOAC discontinuation.…”
Section: Introductionmentioning
confidence: 99%
“…An eczematous drug eruption also was reported in a woman aged 71 years with atrial fibrillation with palmar and plantar involvement 11. To the best of our knowledge, there have been only two reported cases of dabigatran-related LCV: Cakmak et al 12 discussed a woman aged 74 years developing LCV within a week of dabigatran usage, and Potolidis et al 13 reported a case in a man aged 70 years in less than a week of initiation of dabigatran. Both cases were treated with systemic steroids and were switched to other forms of anticoagulation including low molecular heparin and warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this relatively frequent side effect may be related to drug chemical structure as an aromatic amine (36). Three leukocytoclastic vasculitis case reports were found (37,38,39) developing within the first week of treatment with dabigatran with typical purpuric macules, distribution to limbs, back and trunk, and shared histopathologic findings of neutrophilic infiltration, red cell extravasation and fibrin deposition within vessel walls. In the case described by An J. and colleagues (37) cutaneous vasculitis was associated with peripheral blood eosinophilia and elevation of inflammatory markers.…”
Section: Hypersensitivity Reactions To Dabigatranmentioning
confidence: 99%